Convenient Explicit Effects using Type Inference with Subeffects - Leijen, Daan; Tate, Ross (Microsoft Research, 2010)
Most programming languages in use today let one freely use arbitrary (side) effects. This is despite the fact that unknown and unrestricted side effects are the cause of many software problems. We propose a programming model where effects are treated in a disciplined way, and where the potential side-effects of a function are apparent in its type signature. In contrast to most effect systems that are meant for internal compiler optimizations, our system is designed to be used by the programmer. Inspired by Haskell, we use a coarse-grained hierarchy of effects, like |Pure| and |IO|, which makes it convenient to read and write type signatures. The type and effect of expressions can also be inferred automatically, and we describe a polymorphic type inference system based on Hindley-Milner style inference.